The study of Kalasin province online food delivery business chains - Wichachai, Chonlada; Nariso, Arisa; taengphukieo, Ratchada (Journal of Engineering and Industrial Technology, Kalasin University, 2024)
The purpose of this study is to investigate the online food delivery business chain and examine the logistics activities of online food delivery businesses in Kalasin province. According to the study, there are four main categories within the online food delivery business chain: platforms, restaurant partners, service users or customers, and food delivery workers or riders. The platform manages the network to assist businesses in operating systematically to ensure the efficient flow of information, money, goods, and feedback from the service. Following the investigation of the online food delivery business chain, restaurants are upstream, platforms and food delivery workers or riders are midstream, and customers or service users are downstream. The analysis of 13 logistics activities revealed that they all have a connection to restaurants. Midstream is a platform and food delivery driver/rider who is relevant to 10 activities, whereas downstream is a customer who is relevant to 3 activities. Customer service, order processing, reverse logistics, and logistics communications are the primary hubs of the online food delivery business supply chain and can be classified as upstream, midstream, or downstream activities.